LIDAR e Fotogrammetria Digitale verso una nuova integrazione - Rinaudo, Fulvio; Nex, Francesco (GEOmedia, 2012)
In tutte le applicazioni del rilevo metrico la tecnica LIDAR e la Fotogrammetria Digitale giocano ormai un ruoloquasi esclusivo. Gli efficienti servizi forniti dalle reti di stazioni permanenti e dalle piattaforme GNSS/IMU hannoconsentito una rapida diffusione e una affidabilità mai raggiunta per altre tecniche di rilievo in ambito territoriale,cosà¬ come pure nelle applicazioni terrestri quali il rilievo architettonico o il monitoraggio di fenomeni naturali, ovesono stati sostituiti quasi integralmente gli approcci tradizionali del rilievo topografico terrestre. LIDAR and Digital Photogrammetry towards a new integration A new integration approach between digital photogrammetry and LiDAR is presented in this paper. Up to now LiDAR use some photogrammetric topics to manage point clouds and digital photogrammetry extract useful information from LiDAR data to produce traditional and accurate orthophoto. Considering that in traditional photogrammetric plotting the surveyor define the 3D location of the break-lines and add points just in those parts of the object where smooth surfaces can be defined, the proposed solution foresees a continuous exchange of information between those techniques in order to automatically extract the break-lines of the surveyed object. The final results is the complete breack-lines 3D description and the point clouds portions useful to define smooth surfaces. At the end of the automatic procedure a complete 3D set of information is produced in order to build up the fine 3D model of the surveyed object.